An analytical study of psychological stress among Algerian football players in continental and Arab competitions - 2011/2012 -. - GUEMINI, Hafid (sports creativity, 2025)
The primary objective of this study was to determine the impact of psychological stress on the performance of Algerian football players. The research sample consisted of 170 players active in professional football clubs. Our research employed a descriptive-analytical approach to highlight the role of psychological preparation in mitigating stress, as well as how its intensity varies depending on the level of competition and the club's popularity. The study's results indicated a negative impact on player and team performance in general when psychological preparation before competition is inadequate. Furthermore, the players' lack of sporting experience contributes to increased stress levels, hindering their ability to cope effectively with various competitive situations. The study also clearly demonstrated the effects of the level of competition and the club's popularity on stress levels. Finally, the research aimed to propose several suggestions that could contribute to further understanding of the requirements of modern football and the importance of its psychological aspect. This includes activating psychological preparation within Algerian clubs, as it is an effective and crucial tool for preparing and developing players' abilities to compete at their highest potential in major continental and regional competitions.